1998
DOI: 10.1097/00006199-199807000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Geragogy-Based Medication Instruction in the Emergency Department

Abstract: These findings suggest that a medication teaching intervention geared to the special needs of the elderly can be effective in increasing medication knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…It contains concrete language presented in an organized layout, and includes culturally diverse, text-enhancing graphics. (15)(16)(17)(18)(19) It contains the same advance care planning topics as the aforementioned standard form. However, it also contains broader treatment choices, such as providing more options than just to prolong or not to prolong life (the options available in the standard form), but also the options of wanting to prolong life but only for a period of time, being able to refuse certain treatments such as blood transfusions, and having the option of letting the health care agent decide.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…It contains concrete language presented in an organized layout, and includes culturally diverse, text-enhancing graphics. (15)(16)(17)(18)(19) It contains the same advance care planning topics as the aforementioned standard form. However, it also contains broader treatment choices, such as providing more options than just to prolong or not to prolong life (the options available in the standard form), but also the options of wanting to prolong life but only for a period of time, being able to refuse certain treatments such as blood transfusions, and having the option of letting the health care agent decide.…”
Section: Interventionmentioning
confidence: 99%
“…We also incorporated input from the target population (15) and used a clear layout, large 14 point font, appropriate line spacing and margins, and graphics that helped to explain the text. (14,(16)(17)(18)(19) These techniques have been shown to improve acceptability (16,17), activate patients to initiate discussions with providers (17) and, in some cases, enhance understanding. (16,18,19) We then conducted a randomized trial to compare the redesigned to a standard form ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies in other disease models present evidence related to the role of health literacy in learning and retaining self-management skills in patients with other chronic diseases. For example, simplified materials have been shown to improve knowledge (38)(39)(40)(41)(42)(43)(44), health care use (45), and health behaviors (46,47) for patients with diabetes mellitus, rheumatoid arthritis, obesity, and hypertension, irrespective of health literacy. In addition, subjects with low health literacy have been able to learn and retain self- management skills in small studies of heart failure, obesity, and osteoarthritis (48)(49)(50).…”
Section: Table 4 Predictors Of Better Asthma Medication Knowledge Atmentioning
confidence: 99%
“…Medication knowledge was significantly higher for the subjects receiving the customized instructions, assessed by follow-up telephone interview 48-72 hours after discharge. 63 A final consideration is the consistency in the manner in which patient education is delivered in the acute care setting. Although one study in a pediatric ED showed that parents given standardized rather than nonstandardized verbal instructions demonstrated significantly greater knowledge of information of their child's illness, 64 patient education should still be flexible to accommodate the patient's learning needs.…”
Section: Considerations For Instructional Materialsmentioning
confidence: 99%